First Report of Fungus Scopulariopsis Brevicaulis From Fresh Water Dry Shrimp in Bangladesh - Ara, Ismot; Sultana, Roksana; Chanda, Ismath Jahan; Alam, Nuhu (Bangladesh Journal of Zoology, 2020)
Abstract Not Available Bangladesh J. Zool. 48(1): 203-209, 2020